2013
DOI: 10.1155/2013/235190
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance among Pulmonary Tuberculosis Patients in Calabar, Nigeria

Abstract: Background. This study aimed to determine the pattern of drug susceptibility to first-line drugs among pulmonary TB patients in two hospitals in Calabar, Nigeria. Methods. This was a descriptive cross-sectional study carried out between February 2011 and April 2012. Sputum samples from consecutive TB patients in Calabar were subjected to culture on Lowenstein-Jensen (LJ) slopes followed by drug susceptibility testing (DST). The DST was performed on LJ medium by the proportion method. Results. Forty-two of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
34
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 18 publications
(20 reference statements)
11
34
4
Order By: Relevance
“…Rifampicin resistance of 6.6% found in this study is very close to the 7.0% reported in samples collected from Jos and Lagos, Nigeria [11]. Another study in Calabar Nigeria reported a rifampicin resistance of 6%, although they did not find any patient with resistance to only rifampicin [12]. Using BACTEC 960 system for drug susceptibility testing in Abuja, Lawson et al [13] reported that 10 (31%) confirmed tuberculosis samples were resistant to at least one of the four drugs tested including rifampicin, while 4 (13%) were resistant to the four drugs (isoniazid, ethambutol, streptomycin and rifampicin) tested and were classified as multidrug resistant-TB (MDR-TB).…”
Section: Discussionsupporting
confidence: 78%
“…Rifampicin resistance of 6.6% found in this study is very close to the 7.0% reported in samples collected from Jos and Lagos, Nigeria [11]. Another study in Calabar Nigeria reported a rifampicin resistance of 6%, although they did not find any patient with resistance to only rifampicin [12]. Using BACTEC 960 system for drug susceptibility testing in Abuja, Lawson et al [13] reported that 10 (31%) confirmed tuberculosis samples were resistant to at least one of the four drugs tested including rifampicin, while 4 (13%) were resistant to the four drugs (isoniazid, ethambutol, streptomycin and rifampicin) tested and were classified as multidrug resistant-TB (MDR-TB).…”
Section: Discussionsupporting
confidence: 78%
“…The MDRTB prevalence rate of 6.9% found in this study is comparable with 4.0% rate reported in Calabar [13] and 5.8% recorded among TB patients in Abeokuta [15]. A study in Kwara in 2013 by Rasaki et al recorded a prevalence of Rifampicin mono-resistance using GeneXpert to be 7.2% [16].…”
Section: Discussionsupporting
confidence: 82%
“…The second line drugs for treatment of MDRTB are more expensive, not commonly available, have more adverse side effects and with extended treatment duration [13]. The prolonged duration of treatment may further compound issues in view of the socio-economic impact on the patient and his immediate family.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Reported that previous TB treatment was a risk factor for MDR-TB and [20] in a study in South-west Nigeria reported that the most significant factor associated with drug resistance was a history of previous anti-TB treatment. Also, [21] reported that previous TB treatment was significant for drug resistance. [22] In a study in Karnataka region, India, showed that past history of pulmonary TB was statistically associated with development of drug resistance.…”
Section: Discussionmentioning
confidence: 99%